A global comparative analysis of the the inclusion of priority setting in national COVID-19 pandemic plans: A reflection on the methods and the accessibility of the plans (2024)
ABSTRACT: Background: Despite the swift governments' response to the COVID-19 pandemic, there remains a paucity of literature assessing the degree to which; priority setting (PS) was included in the pandemic plans and the pandemic plans were publicly accessible. This paper reflects on the methods employed in a global comparative analysis of the degree to which countries integrated PS into their COVID-19 pandemic plans based on Kapiriri & Martin's framework. We also assessed if the accessibility of the plans was related to the country's transparency index. Methods: Through a three stage search strategy, we accessed and reviewed 86 national COVID-19 pandemic plans (and 11 Canadian provinces and territories). Secondary analysis assessed any alignment between the readily accessible plans and the country's transparency index. Results and conclusion: 71 national plans were readily accessible while 43 were not. There were no systematic differences between the countries whose plans were readily available and those whose plans were 'missing'. However, most of the countries with 'missing' plans tended to have a low transparency index. The framework was adapted to the pandemic context by adding a parameter on the need to plan for continuity of priority routine services. While document review may be the most feasible and appropriate approach to conducting policy analysis during health emergencies, interviews and follow up document review would assess policy implementation.